-6(2s+4)=

Simple and best practice solution for -6(2s+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2s+4)= equation:


Simplifying
-6(2s + 4) = 0

Reorder the terms:
-6(4 + 2s) = 0
(4 * -6 + 2s * -6) = 0
(-24 + -12s) = 0

Solving
-24 + -12s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + -12s = 0 + 24

Combine like terms: -24 + 24 = 0
0 + -12s = 0 + 24
-12s = 0 + 24

Combine like terms: 0 + 24 = 24
-12s = 24

Divide each side by '-12'.
s = -2

Simplifying
s = -2

See similar equations:

| -2(j+18)=-4 | | -2(3r+1)-5(r-11)= | | 7sin^2(x)-cos^2(x)=6 | | y=x^2-6+6 | | 3z-1=0 | | (4z+2)(5-z)=0 | | d^2y/dx^2-9y=x | | 3(x-44)=18 | | 14-c=10 | | 2x+7=9x+7 | | 2x(x-2)=x^2 | | r-8/2=4 | | 16x+3=21x-7 | | 2x^2+7x-15=f(x) | | 7-3(6n-2)=-2n-35 | | 11d+8=7d+24 | | -12/p=3 | | ((120*2x)/2)=4x | | 5(2x-4)-9x=6 | | 3s-4=14 | | 2y^2-y+53=(y+5)(y+5) | | 7x-4y+12=0 | | 2(d-5)=18 | | 7(4y-9)= | | g^6+12g^3+36=0 | | 4a+27=9n-8 | | 2v^2+9v-10=(v+2)(v+2) | | 7c^2-21c+14=0 | | 4z-16=2+2 | | 2(w-20)=-16 | | 2x^2+23x+67=(x+7)(x+7) | | p^2-16pq+63q^2=0 |

Equations solver categories